Relationship Between Work Stress and Nurse Work Shifts with Implementation of Patient Safety During Covid-19 - Serri Hutahaean; Nada Mutiara (Universitas Muhammadiyah Yogyakarta, 2022)
The increase in Covid-19 cases has made nurses who handle Covid-19 patients feel work stress, which has led to poor patient safety implementation. Irregular work shift schedules for nurses can also lead to errors and poor patient safety implementation. The purpose of this study was to determine the relationship between work stress and nurses' work shifts in the Inpatient Room of RSUD X during the Covid-19 pandemic. This research method uses descriptive-analytic with a cross-sectional design. The data collection period is in June 2021. Sampling was carried out using the purposive sampling technique. The sample of this research is 48 nurses in the Inpatient Room. The research instrument used the IPSG questionnaire which was adopted from the Nasution questionnaire, (2013) and the NIOSH Generic Job Stress Questionnaire questionnaire. The results were analyzed using the chi-square test, indicating that there was a significant relationship between work stress and the implementation of patient safety (p=0.010) and there was a significant relationship between work shifts and the implementation of patient safety (p=0.022). It can be concluded that there is a significant relationship between work stress and nurse work shifts and the application of patient safety during the Covid-19 pandemic. Hospital management needs to pay attention to the mental condition of nurses, increase the number of workers and organize effective work shifts during the Covid-19 pandemic.